Empowering Pesantren: A Study of Al-Ghazali’s Thoughts on Islamic Education - Umi Zulfa (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2018)
Efforts to create peaceful world by upholding values of pluralism and to bring prosperity on earth by developing science and technology become very crucial and urgent. However, horizontal conflicts due to religious differences and technological abuses are still prevalent. This study provides an alternative design for Islamic education that is believed to be able to make life on earth more advanced, peaceful and prosperous with reference to al-Ghazali’s thoughts. It reveals some possible ways to empower pesantren to meets the needs of students in the contemporary era, extracted from al-Ghazali’s thoughts on shak, tawāḍu‘, ṣuḥbah, mukhtalif al-alwān and the classification of knowledge. The study is qualitative research with descriptive analysis of literatures concerning education. In this paper, the author argues that such an ideal pesantren should uphold the characteristics of (1) inclusive religious education, (2) balanced religious and scientific development, (3) student-centered learning, and (4) entrepreneurial institution.